Wind load investigation of self-supported lattice transmission tower based on wind tunnel tests. (1st February 2022) - Zhang, Wentong; Xiao, Yiqing; Li, Chao; Zheng, Qingxing; Tang, Yanan
Highlights: The same model is designed to perform the aeroelastic wind tunnel and HFFB tests; The unfavorable wind attack angles of the transmission tower are determined; The characteristics of the generalized PSDs of wind forces are specified; The empirical formulas of the generalized PSDs of wind forces are established; The nonlinear mode shape correction factor for the transmission tower is derived. Abstract: Through a series of wind tunnel tests on a self-supported lattice transmission tower model, the wind loads on the tower were investigated in this paper. According to similarity laws, the scaled tower model was designed and fabricated, and the atmospheric boundary layer wind field of Category-B specified in Chinese load code was simulated in the wind tunnel laboratory. Based on the aeroelastic wind tunnel tests and the high frequency force balance tests, the dynamic vibrations, the nondimensional wind force coefficients and the generalized power spectral densities (PSDs) of dynamic wind forces were analyzed and discussed. For the convenient application, the empirical formulas of the generalized PSDs of dynamic wind forces were established and the nonlinear mode shape correction was introduced, which were verified via comparison between the aeroelastic tests and the calculated dynamic responses of tower top. It is indicated that the unfavorable wind attack angles may happen around θ = [15° 30°] and θ = [60° 75°] for this type of tower; the generalized PSDs of wind forces are unimodal in shape, and the corresponding effective bandwidths and the nondimensional frequencies of peaks vary with the wind attack angle θ, especially those of the cross-wind forces are larger than those of the along-wind forces obviously; the established empirical formulas of the generalized PSDs of dynamic wind forces and the derived nonlinear mode shape correction factor are applicable.